2021
DOI: 10.2166/wst.2021.425
|View full text |Cite
|
Sign up to set email alerts
|

Modelling temperature dynamics in sewer systems – comparing mechanistic and conceptual modelling approaches

Abstract: The vast majority of the energy consumed for urban water services is used to heat tap water. Heat recovery from wastewater is consequently an area of rapidly growing concern, both in research and by commercial interest, promoting the path towards a circular economy. To facilitate a system-wide evaluation of heat recovery from wastewater, this paper compares two one-dimensional models (mechanistic and conceptual) that can describe wastewater temperature dynamics in sewer pipe systems. The models are applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…The lower source of energy in heat pumps can be both wastewater from individual systems [77] and those from extensive communal systems [131,132]. In the latter case, wastewater is discharged Wastewater heat recovery technology using heat pumps is successfully applied in Scandinavian countries as well [125]. Even in less developed countries, the first investments are currently being made to recover deposited heat energy from wastewater.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower source of energy in heat pumps can be both wastewater from individual systems [77] and those from extensive communal systems [131,132]. In the latter case, wastewater is discharged Wastewater heat recovery technology using heat pumps is successfully applied in Scandinavian countries as well [125]. Even in less developed countries, the first investments are currently being made to recover deposited heat energy from wastewater.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…Wanner et al [19] demonstrated that reducing the temperature of raw wastewater by just 1 • C can lead to a 10% increase in the required capacity of the nitrification chamber. Hence, each investment in a raw wastewater heat recovery installation requires an individual approach and detailed analysis, for example, using dedicated computer simulation software [125]. In some cases, the optimal solution may involve only slight cooling of the wastewater, while in other circumstances, the construction of a bypass may be necessary.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%